Financial structure effects on export intensity and diversification: The case of Portuguese industrial firms - Pacheco, Luís Miguel (2018)
The objective of this paper is to empirically examine the relationship between a set of financial variables and export performance. Though many empirical papers studied the impact of financial structure on firms’ performance its effect on firms’ export performance has been less studied. The primary objective of our paper is to fill that gap, particularly for the case of Portugal, focusing on SMEs, where agency problems and lack of resources could impact more on export performance. Using a panel data methodology and considering a sample of 3.164 Portuguese manufacturing SMEs for the period 2011-2014 our results indicate that SMEs with less debt, higher profitability and of greater size tend to present higher export intensity and diversification. This exploratory paper gives a contribution to clarify which are the main financial determinants of an export-oriented firm, which is an important issue not only for managers but for all the stakeholders, particularly policy makers aiming to promote outward orientation of domestic firms.